Remodelación del "Centro Comercial Aeropuerto" - Fernández Jaramillo, Alejandro Santiago (2013)
The remodeling project of “Centro Comercial Aeropuerto” consists on preserving the actual structure and improving the esthetics of the neighborhood its located in. “La Prensa” is known for being a commercial zone and this is the main Mall of the area. For a long time it has been neglected and it has never reached its full potential. The interventions main purpose is to make the Mall not only a selling spot, but too also make it a place where customers can go and hang out. The plan is to revive the old concept of the of the Pasaje Comercial with a central plaza and classic architectural elements. With the application of a concept the areas will be shaped into a department store look alike distribution, with wide halls and large stores. The project is a mix of modernity and classism, both combined to create a harmonious space that its style does not age with time. Functionality is the main goal and the ideal balance between furniture, lighting, flooring, textures, ceilings, and shapes. The main objective is to satisfy every customers need in different zones located strategically throughout the mall. But too also create a shopping experience, where the customer feels pleased and wants to return.